Biofuels and vertical price transmission: The case of the U.S. corn, ethanol, and food markets - Dusan Drabik; Pavel Ciaian; Jan Pokrivcak (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2014)
This is the first paper to analyze the impact of biofuels on the price transmission along the food chain. We analyze the U.S. corn sector and its vertical links with food and ethanol (energy) markets. We find that biofuels affect the price transmission elasticity in the food chain compared to a no biofuel production situation but the effect depends on the source of the market shock and the policy regime: the price transmission elasticity declines under a binding blender's tax credit and a food market shock. Our results also indicate that the response of corn and food prices to shocks in the corn and/or food markets is lower in the presence of biofuels. Finally, the sensitivity analyses indicate that our results are robust to different assumptions about the model parameters.
Keywords: Q11; Q21; 330; price transmission; food chain; biofuels; prices